AmeÌrique Septentrionale en 1540 - HouzeÌ, A.
This map shows North and Central America and the surrounding areas. Each country or region is outlined in color and labeled. Major cities and bodies of water are marked. There are several notations on areas throughout the map and there is text beneath the map with information regarding explorations and discoveries with a color key. Scale [ca. 1:33,333,333].